Permasalahan sampah kota Makassar studi kasus TPA Tamangapa - Rusni, Nur Khafifah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The waste issue in developing countries such as Indonesia is a problem that seems to never be resolved, mainly due to improper handling by all parties involved. Over time, this will affect the environmental balance. If this issue is not taken seriously, the amount of generated waste will increase every year, in line with the higher population growth and development. Makassar is one of the cities facing waste problems, especially at the final disposal site called TPA Tamangapa. The TPA Tamangapa covers an area of 16.8 hectares with a waste capacity of 927,749.76 m3, but in reality, the waste volume from 2015-2019 has exceeded the maximum limit at 946,441.37 m3. The identified problems in this research are: TPA Tamangapa has been in an overcapacity status since 2019 and still uses an open dumping system, which has the most significant negative impact on the environment, and the waste reduction efforts at TPA Tamangapa in Makassar are not yet optimal. The method used is literature review, identifying, evaluating, and analyzing existing research and journals. Additional data are obtained from the BPS Makassar and UPTD Tamangapa. In conclusion, addressing the overcapacity issue of TPA Tamangapa in Makassar since 2019 requires special attention and appropriate actions from the government and the involvement of all parties. Reducing the amount of waste can be achieved by maximizing waste separation from its source, thereby optimizing the performance of local scavengers who play a significant role in reducing waste at TPA Tamangapa in Makassar.